Воспитание толерантности в условиях социокультурной среды образова-тельного учреждения - Дайкер, А.Ф. (My University, 2013)
Article is devoted to the problem of tolerance formation of future teachers. The article considers the concept of "tolerance", "environment of high school," pedagogical conditions and methods aaktivnye tolerance education of future teachers.